2020
DOI: 10.1016/j.jebo.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Drip pricing and its regulation: Experimental evidence

Abstract: We experimentally examine the effects of drip pricing on seller strategies and buyer behavior as well as the implications for regulation. Sellers set two prices: a base price and a drip price. At first, buyers only observe the base prices and make a tentative purchase decision. Revealing the sellers' drip prices, however, comes at a cost. We find that sellers only compete in base prices and set the highest possible drip price. This makes the base price a reliable indicator for the lowest total price, and few c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Furthermore, children have been shown to be particularly prone to be affected by dark patterns in advertising in apps (Meyer et al, 2019[137]) and in the design of loot boxes in online games (Forbrukerrådet, 2022[89]), particularly where they incentivise spending and personal data sharing (Bell and Fitton, 2021 [138]). Radesky et al (2022 [58]) furthermore found children of families of low socio-economic status were more likely to encounter manipulative design features in children's apps.…”
Section: Consumer Vulnerability To Dark Patternsmentioning
confidence: 99%
“…Furthermore, children have been shown to be particularly prone to be affected by dark patterns in advertising in apps (Meyer et al, 2019[137]) and in the design of loot boxes in online games (Forbrukerrådet, 2022[89]), particularly where they incentivise spending and personal data sharing (Bell and Fitton, 2021 [138]). Radesky et al (2022 [58]) furthermore found children of families of low socio-economic status were more likely to encounter manipulative design features in children's apps.…”
Section: Consumer Vulnerability To Dark Patternsmentioning
confidence: 99%
“…The customer can be engaged in a purchasing process by attractive features such as low pricing, which leads to a surprise when the total price is discovered. Spending time on subsequent pages will prevent her from remembering the competition's price or prevent her from starting the search process from the beginning [38].…”
Section: Consumer's Behavior Manipulationmentioning
confidence: 99%
“…Most of the legal debate internalizes a demand approach, centred on eliciting consumers' response to specific practices (Huck & Wallace, 2015), thereby limiting the scope of the analysis. Industrial economists have paid more attention to the supply side, studying the consequences of the use of shrouding and complexity as anti-competitive tools (Kalayci & Potters, 2011;Gu & Wenzel, 2015Kalaycı, 2016;Crosetto & Gaudeul, 2017;Normann & Wenzel, 2019;Rasch et al, 2020). However, this body of literature continues to overlook the endogenous choice of practices from a menu of options (instead of a simple extensive margin) and misleading use (instead of simple adoption).…”
Section: Policy Background and Related Literaturementioning
confidence: 99%
“…The transaction test in the US is interpreted as the inducement of a net loss, that is, the benefits do not adequately compensate the buyer for the price paid (Luguri & Stahilevitz, 2021). endogenous choice of options is the paucity of proposed protective measures, which are usually limited to either prohibition (Rasch et al, 2020) or increasing market entry (Kalaycı, 2016).…”
Section: Policy Background and Related Literaturementioning
confidence: 99%